MECHANISMS OF DESTRUCTION AND SYNTHESIS OF LIQUID MEDIA, USED IN THE FOOD INDUSTRY UNDER NON-EQUILIBRIUM CONDITIONS - T. V. Savenkova; A. R. Karimov; M. A. Taleysnik; T. V. Gerasimov; N. B. Kondratev (Пищевые системы, 2019)
The formation of food liquid medium structures containing at least 70 % of disperse particles with high dispersiveness has been considered. The possible formation mechanisms of food liquid medium structure when slow (hydrodynamic) and quick (acoustic) processes create favorable conditions for cavitation have been studied. The possibility to control these processes for initiation of mechanical and kinetic reactions that change the structure of the medium has been demonstrated. The invert syrup has been selected as the study object. The change in the invert syrup structure before and after such cavitation treatment has been recorded with the use of metallographic microscope Nikon Eclipse MA100. The decrease in disperse phase sizes from 2–3 µm to 0.1–0.4 µm along with establishing the high uniformity of component distribution as compared to the syrup without cavitation process treatment has been detected.